Dynamics of Psychopathology During Psychiatric Support in Patients with Chronic Pain - Asanova, Azize (Psychosomatic Medicine and General Practice, 2026)
Background. Chronic pain is among the clinical conditions most closely associated with mental disorders. Contemporary evidence indicates that mental disorders not only co-occur with chronic pain but may also contribute directly to its onset and maintenance, influencing pain intensity, pain duration, functional impairment, and treatment outcomes. At the same time, timely psychiatric assessment and management of psychopathological symptoms are increasingly recognized as essential components of comprehensive chronic pain care. Despite the high prevalence of mental disorders among patients with chronic pain, their early identification and treatment remain insufficiently integrated into routine clinical practice. Objective. To evaluate the clinical effectiveness of proactive personalized psychiatric support in patients with different types of chronic pain by assessing changes in psychopathological symptoms and pain intensity during treatment follow-up. Materials and Methods. A prospective cohort clinical psychopathological study with an interventional phase was conducted among 302 patients with different types of chronic pain who completed the full course of treatment and follow-up. Participants were stratified into five clinical groups: Primary Psychogenic Pain (PPP1), Primary Psychophysiological Pain (PPP2), Mixed Primary Psychogenic and Psychophysiological Pain (PPP3), Secondary Mixed Pain (SMP), and Secondary Organic Pain (SOP). Clinical verification of non-psychotic mental disorders (NPMDs) was performed within the framework of proactive personalized psychiatric support according to ICD-10 diagnostic criteria, with consideration of the updated ICD-11 classification. Changes in anxiety and depressive symptoms were assessed using the Hospital Anxiety and Depression Scale (HADS), while pain intensity was evaluated using the Visual Analogue Scale (VAS) at baseline and at 1, 3, 6, and 12 months after treatment initiation. Results. Among the 302 patients with chronic pain, mental disorders were verified in 176 (58.3%) individuals. According to repeated psychiatric assessment, all identified mental disorders had achieved either full or partial remission by the end of the follow-up period. Complete remission of clinically significant anxiety and depressive symptoms, as measured by the Hospital Anxiety and Depression Scale (HADS), was observed across all study groups within the spectrum of non-psychotic mental disorders (NPMDs) and affective syndromes by the end of follow-up. The most pronounced improvement was observed in the Primary Psychogenic Pain (PPP1), Mixed Primary Psychogenic and Psychophysiological Pain (PPP3), and Secondary Mixed Pain (SMP) groups, which demonstrated the highest baseline psychiatric and psychopathological burden. HADS scores decreased significantly in all groups (p<0.001), with the greatest changes occurring during the first 3–6 months following treatment initiation. Concurrently, a significant reduction in pain intensity, as measured by the Visual Analogue Scale (VAS), was observed across all groups (p<0.001), and this improvement was maintained throughout the follow-up period. Conclusions. Proactive personalized psychiatric support demonstrated effectiveness in achieving full or partial remission of mental disorders and reducing the severity of affective syndromes in patients with different types of chronic pain. The observed outcomes underscore the clinical importance of integrating psychiatric care within interdisciplinary chronic pain treatment frameworks. Keywords: chronic pain, mental disorders, depression, anxiety, HADS, proactive psychiatric support, personalized treatment.